2012
DOI: 10.1007/s11695-012-0761-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Greater Curve Plication in Asia: Initial Experience

Abstract: LGCP is safe and effective in achieving significant weight loss in obese ethnic Chinese patients. However, weight loss in BMI <35 is more pronounced. It is a very valid alternative to other procedures in Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
1
23
1
1
Order By: Relevance
“…The overall %EWL was significantly higher for the group with a BMI o 45 kg/ m 2 compared to those who had a BMI 4 45 kg/m 2 (69.86% versus 55.49%); the percentage of inadequate weight loss was doubled for the higher compared to the lower BMI group (36% versus 18%). Another study by Mui et al [6] found that weight loss in the group with a BMI o 35 kg/m 2 is more pronounced than that in the group with a BMI 4 35 kg/m 2 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The overall %EWL was significantly higher for the group with a BMI o 45 kg/ m 2 compared to those who had a BMI 4 45 kg/m 2 (69.86% versus 55.49%); the percentage of inadequate weight loss was doubled for the higher compared to the lower BMI group (36% versus 18%). Another study by Mui et al [6] found that weight loss in the group with a BMI o 35 kg/m 2 is more pronounced than that in the group with a BMI 4 35 kg/m 2 .…”
Section: Discussionmentioning
confidence: 94%
“…The full text of the remaining 17 articles was reviewed for eligibility. Fourteen [3][4][5][6][7][8][9][10][11][12][13][14][15][16] of the above 17 articles were selected for this review ( Table 1). The authors excluded one article [17] which was a letter commenting on another article, one article [18] which reported American Society for Metabolic and Bariatric Surgery policy on gastric plication, and another article [2] which was a substudy of a larger series by the same group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors prefer 2 rows of running sutures, some used 2 rows of interrupted sutures and others recommend a combination of running and interrupted sutures. 3,7,8,10,11,16,17,20,21 Inner layer sutures are better to be taken in an interrupted manner to adjust the plication and to avoid suture breaking of continuous layer leading to failure. The outer layer should be running stitch to avoid herniation in between.…”
Section: Resultsmentioning
confidence: 99%